Experimental Comparison of Telepsychiatry and Conventional Psychiatry for Mentally Ill Parolees in California, 2011-2015 - Farabee, David ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The main goal of the study was to empirically measure the effectiveness of Telepsychiatry for mentally ill parolees.Parolees enrolled in the study were assigned to either face-to-face sessions with their psychiatrists for the duration of their treatment or telepsychiatry sessions with their psychiatrist, in which the parolees interacted with their assigned psychiatrist via a web-based screen interface. Administrative records data on recidivism was collected for everyone who consented to be randomized in this study.